(untitled) (Chicago, 2000)
This book introducing JavaServer pages. The basics, beneath JSP. JSP and JavaBeans, JSP sessions. Error handing with JSP. Java database connectivity and connection pooling...
Keywords: Máy chủ,Web servers; Chương trình máy tính,Computer programs